Web Company Profile CV. Priyandra Inarya Cipta: Develop a website company profile - Agung Kridoyono; Aris Sudaryanto (Journal of Science and Social Development, 2021)
This article is a journal devotion for society that doing by educational institution especially us as a lecture to implement the threefold missions of higher education known as tridarma college. We develop a website company profile at public business that did not have the web company profile, the name of the corporate is Priyandra Kinarya Cipta which location is 10mil from the location of our institutional college. So we make a website company profile and the component in order to this company can be known by electronic media. Hopefully this role for the company to commerce the product and the business.   Keywords: web site company profile, electronic media